Challenges in wireless communication for connected sensors and wearable devices used in sport biofeedback applications - Kos, A.; Milutinovic, V.; Umek, A. (Future Generation Computer Systems, 2019)
Sensors, wearables, wireless networks, and other Internet of Things technologies are ever more present in our daily life. We study their applicability and use in biofeedback systems and applications in sport. Biofeedback systems are important in motor learning where a person in the loop uses the feedback information to influence the execution performance. Sensors, actuators, and wireless technologies come in great varieties regarding their properties. We describe the most common groups of sensors and actuators that are used in sport and list the most widespread and easily available wireless technologies. We present the most important constraints of a biofeedback system operation and define a number of fundamental architectures of biofeedback systems. Taking into account all of the above, we present a number of different biofeedback application scenarios in sports. We match the scenarios to the most appropriate existing wireless technology that is expected to sustain scalability in the number of nodes or increased data rates for the expected application lifetime. We find out that currently none of the existing wireless technologies can satisfy the variety of demands of different biofeedback application scenarios.